2011
DOI: 10.1007/s10719-011-9333-6
|View full text |Cite|
|
Sign up to set email alerts
|

N-Glycosylation profiling of recombinant mouse extracellular superoxide dismutase produced in Chinese hamster ovary cells

Abstract: Extracellular superoxide dismutase (EC-SOD), the major SOD isoenzyme in biological fluids, is known to be N-glycosylated and heterogeneous as was detected in most glycoproteins. However, only one N-glycan structure has been reported in recombinant human EC-SOD produced in Chinese hamster ovary (CHO) cells. Thus, a precise N-glycan profile of the recombinant EC-SOD is not available. In this study, we report profiling of the N-glycan in the recombinant mouse EC-SOD produced in CHO cells using high-resolution tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Since N-glycans of human and mouse EC-SOD were both reported to possess a core-fucose structure [16,33], we also checked whether deletion of core-fucose affects EC-SOD secretion, by using HEK293T cells lacking the core-fucose-synthesizing enzyme FUT8 [35]. The presence of core-fucose on wild-type EC-SOD was confirmed by its reactivity with PhoSL lectin (Fig.…”
Section: Conserved Glycosylation Of Ec-sod Is Essential For Its Secrementioning
confidence: 99%
See 2 more Smart Citations
“…Since N-glycans of human and mouse EC-SOD were both reported to possess a core-fucose structure [16,33], we also checked whether deletion of core-fucose affects EC-SOD secretion, by using HEK293T cells lacking the core-fucose-synthesizing enzyme FUT8 [35]. The presence of core-fucose on wild-type EC-SOD was confirmed by its reactivity with PhoSL lectin (Fig.…”
Section: Conserved Glycosylation Of Ec-sod Is Essential For Its Secrementioning
confidence: 99%
“…Notably, a naturally occurring mutation in the C-terminal region (R213G) that dramatically reduces the affinity to heparin was found in humans [28]. Previous glycan analyses of recombinant mouse and human EC-SODs showed that they are mainly modified with complextype N-glycans with core-fucose and sialic acids [16,33], but the physiological functions of the EC-SOD glycan are poorly understood. Positions of the N-glycosylation site and cysteine residues are indicated in the overview diagram.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Purified N-glycans were quantitatively determined based on the peak areas by weak anion-exchange chromatography on a DEAE-5PW column (27). The neutral fraction (flow-through from the anion exchange column) was further separated by reversed-phase HPLC to quantify high mannose and asialo complex type N-glycans separately (28).…”
Section: Graphite Carbon Lc-esi-ms and Esi-ms/ms For Isotopomers Analmentioning
confidence: 99%
“…Total N-glycans derived from both cell lines were separated by anion exchange chromatography according to their sialic acid content (27), and neutral N-glycans were further analyzed by reversed-phase mode (supplemental Fig. S8) (28). As shown in Fig.…”
Section: Quantitative Analysis Of N-glycans and Secreted Hyaluronicmentioning
confidence: 99%